2022
DOI: 10.1364/ol.469291
|View full text |Cite
|
Sign up to set email alerts
|

Self-starting spatiotemporal mode-locking using Mamyshev regenerators

Abstract: Bridging multi-mode fibers and Mamyshev regenerators holds promise for pulse energy scaling in fiber lasers. However, initialization of a multi-mode Mamyshev oscillator remains a practical challenge. Here we report self-starting spatiotemporal mode-locking (STML) in a multi-mode Mamyshev oscillator without active assistance. The first initialized mode-locking is unstable, but stable STML can be attained by increasing the filter separation. Simulations verify the capability of reaching self-starting STML using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…[44,120,121] Cao et al initiated the STML Mamyshev oscillator by adjusting the filter separation alone. [121] However, this method is inconvenient and impractical for large applications because the filter is located within the laser cavity.…”
Section: Starting With Pump Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[44,120,121] Cao et al initiated the STML Mamyshev oscillator by adjusting the filter separation alone. [121] However, this method is inconvenient and impractical for large applications because the filter is located within the laser cavity.…”
Section: Starting With Pump Modulationmentioning
confidence: 99%
“…[59] Furthermore, many researchers have attempted to start MO by adjusting the separation of the filters alone and demonstrated the feasibility of this method in numerical simulations and experiments. [44,120,121] Cao et al initiated the STML Mamyshev oscillator by adjusting the filter separation alone. [121] However, this method is inconvenient and impractical for large applications because the filter is located within the laser cavity.…”
Section: Starting With Pump Modulationmentioning
confidence: 99%
“…Intriguing nonlinear effects such as soliton molecules, [ 13 ] self‐similar pulse, [ 14 ] and beam self‐cleaning [ 15,16 ] were achieved in STML lasers at 1 μ$\umu$m. Cavities incorporated with Mamyshev regenerators [ 17 ] and large‐modal dispersion [ 18 ] can be implemented in STML lasers to extend the performance. Visible‐wavelength STML laser was also reported at 635 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Spatiotemporal mode-locking in the multimode Mamyshev oscillator and its self-starting operation were investigated. 9,10 Spatiotemporal mode-locking in the visible wavelength region was realized in a Pr 3+ /Yb 3+ codoped fiber laser. 11 By using fiber-based components, all-fiber STML lasers were realized.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that spatiotemporal mode-locking could also be achieved in multimode cavities composed of MMFs with large modal dispersion, where passive nonlinear auto-selection of single-mode mode-locking and transition between multimode Q -switching and spatiotemporal mode locking were observed. Spatiotemporal mode-locking in the multimode Mamyshev oscillator and its self-starting operation were investigated. , Spatiotemporal mode-locking in the visible wavelength region was realized in a Pr 3+ /Yb 3+ co-doped fiber laser . By using fiber-based components, all-fiber STML lasers were realized. Automatic spatiotemporal mode-locking was achieved in an MMF laser by using genetic wavefront shaping .…”
Section: Introductionmentioning
confidence: 99%